Monitoring recovery of overgrazed lichen communities on Hagemeister Island, southwestern Alaska - Patrick Walsh; Trevor Goward (Rangifer, 2021)
Understanding the recovery rate of overgrazed lichen communities has value to mangers of lands in northern regions.  We describe lichen community composition and present recovery rate measurements for a 12-year period following overgrazing by reindeer (Rangifer tarandus) on Hagemeister Island, Alaska.  Reindeer were removed from the island in 1993 following overgrazing and average total lichen biomass increased from 504.2 kg/ha (SD 205.4) in 2003 to 795.3 (SD 489.6) in 2015.  We estimate time to recovery with three competing growth curves which estimate grazeable biomass may be reached in 34-41 years.  However, estimates of full recovery to climax biomass varied among the models, ranging from 71 to 400 years.   In 2015, lichen communities were composed of various mixtures of at least 78 lichen taxa, and were dominated by Cladina stygia and other important reindeer forage species.   While reindeer overgrazing diminished forage quantity, it did not extirpate preferred forage taxa.